Self-conscious emotions and depression: Rumination explains why shame but not guilt is maladaptive - Orth, Ulrich; Berking, Matthias; Burkhardt, Simone (Personality and social psychology bulletin, 2006)
Feelings of shame and guilt are factors associated with depression. However, studies simultaneously investigating shame and guilt suggest that only shame has a strong unique effect, although it is not yet clear which psychological processes cause shame and not shame-free guilt to be related to depression. The authors hypothesized that shame, in contrast to guilt, elicits rumination, which then leads to depression. Therefore, in this study we investigated event-related shame and guilt, eventrelated rumination, and depression among 149 mothers and fathers following family breakup due to marital separation. Data were analyzed using latent variable modeling. The results confirm that shame but not guilt has a strong unique effect on depression. Moreover, the results show that the effect of shame is substantially mediated by rumination. The results are discussed against the background of self-discrepancies and self-esteem. © 2006 by the Society for Personality and Social Psychology, Inc.
Created from Fastlane, Scopus look-up
Keywords: Depression; Guilt; Negative life events; Rumination; Shame